Społeczne konstruowanie rytuałów i symboli akademickich - Grzesiak, Emilia (Studia Edukacyjne, 2019)
Rites and ceremonies are very important in university reality. They are extremely important for maintaining the continuity of academic values and highlighting the rank of certain events, which is particularly visible during various academic ceremonies. This article will be devoted to academic rituals, ceremonies and symbols in the context of their social meaning and values. I refer this issue to other dimensions of socio-cultural reality (including ceremonial court practices), I will look for similarities, explaining their significance and roles. I will try to justify how – regarding their long history and tradition – we can understand them in the 21st century.